Peningkatan Hasil Belajar Melalui Diskusi Kelompok Pada Mata Diklat Ilmu Bahan Bangunan Kelas X Teknik Bangunan SMK Negeri 5 Padang - 469-476 , Elwahyudi (CIVED, 2014)
Abstrac This research aims to see and know the improvement of learning outcomes through group discussion on Construction Materials Sciencesubjectof tenth grade students in SMK Negeri 5 Padang.This research uses experimental approach;population of the research is student grade X of Construction Engineering at SMK Negeri 5 Padang enrolled in the academic year 2013/2014. The sampling technique is done by simple random sampling.The gathering of the data uses a test of learning results in the form of 10 objective questions and 2 essay question.From the result of test research, there has been obtained an average value of students who learned using discussion groups that is 81.46 while students who used conventional methods is lower at 77,12,with 2.201 of thitungand 2.011 of ttabel. According to the statement of the hypothesis ifthitung> ttabelitmeans that the null hypothesis (Ho) is rejected and the second hypothesis (H1) that is received. Thus it can be concluded that the learning outcomes of students who are taught by a group discussion method was higher than students who are taught by conventional methodin Construction Materials Science subject for students grade X of SMK Negeri 5 Padang. Keywords:         Learning Outcomes, Group Discussion, Construction Materials Science subject